Exchange Rate, Price Level and Divergences: A Regional Analysis for the Argentine Republic - Pizarro Levi, Ernesto Gabriel (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This paper studies the relationship between the exchange rate and the price level in regional settings for the Argentine Republic. It is considered that exchange rate  fluctuations have a dissimilar influence on the price indices faced by the six regions that form the Argentine territory, according to the classification of the National Institute of Statistics and Census (INDEC, by its acronym in Spanish). The exchange rate, the national consumer price index and the consumer price indices of each region are used as  variables. The empirical analysis is carried out using descriptive statistics and the application of econometric methods of cointegration and common cycles in order to know the correspondence between the variables both in the short and long term. The results show that exchange rate variations influence in different ways the prices of the different regions that make up the Argentine Republic. Likewise, there are significant differences between the results obtained at the national level and for each region both in the short and long term. The latter suggests the existence of particular regional heterogeneities that imply different effects of the exchange rate on prices throughout the country.